Kosovo : Operational Procurement Review - World Bank (Washington, DC, 2013)
This Operational Procurement Report (OPR) provides an assessment of the public-sector procurement system in Kosovo, including that on the legislative framework, the responsibilities and capacity of the institutions entrusted with regulatory and review powers, the efficacy of current procurement practices, and on the environment. The report makes recommendations to bring about legislative, institutional and procedural improvements in the conduct of public procurement, and to bolster the capacity of public-sector institutions to conduct procurement. The report also examines the performance of procurement in projects financed by the Bank, assesses the fiduciary risk to Bank funds from procurement operations in Kosovo, and makes recommendations for the design of procurement arrangements on new Bank-financed projects, and for future supervision of procurement to mitigate that risk. Among the various report recommendations, outlined are the enactment of a transitional legal instrument and completion of the legislative framework for public procurement. Furthermore, greater transparency and accountability of public officials conducting procurement transactions should be ensured, while technical capacity for public procurement should be built within the public sector. Most importantly, over the medium term, the new Law on Public Procurement should be amended.